2018
DOI: 10.1016/j.matbio.2018.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of the extracellular matrix in aortic aneurysmal diseases

Abstract: Aortic aneurysms are morbid conditions that can lead to rupture or dissection and are categorized as thoracic (TAA) or abdominal aortic aneurysms (AAA) depending on their location. While AAA shares overlapping risk factors with atherosclerotic cardiovascular disease, TAA exhibits strong heritability. Human genetic studies in the past two decades have successfully identified numerous genes involved in both familial and sporadic forms of aortic aneurysm. In this review we will discuss the genetic basis of aortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 142 publications
(177 reference statements)
0
15
0
1
Order By: Relevance
“…It is known that components of the ECM, SMC, and members of TGF‐β signaling pathways are crucial for normal structural integrity and development of the vessel wall . Hence, gene mutations that are involved in the above‐mentioned functions contribute to AD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that components of the ECM, SMC, and members of TGF‐β signaling pathways are crucial for normal structural integrity and development of the vessel wall . Hence, gene mutations that are involved in the above‐mentioned functions contribute to AD.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain AD‐related genes, we searched in the Online Mendelian Inheritance in Man database (http://omim.org/), performed a comprehensive literature search, and used the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways (http://www.genome.jp/kegg/pathway.html) and Gene Ontology (http://www.geneontology.org) databases. Finally, by comparing the identified AD‐associated genes, 142 AD‐associated genes were selected for analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, some of these familial TAA patients harbor established monogenic forms of disease, like Marfan or Loeys-Dietz syndromes. However, it is reported that up to 20% of individuals with thoracic disease do not have a syndrome but do have related family members with disease (Familial Thoracic Aortic Aneurysm and Dissection or FTAAD) [ 27 ]. The risk factors associated with AAA include increasing age, male sex and lifestyle-related risk factors, like smoking, hypertension and hypercholesterolemia, which share many risk factors with atherosclerotic cardiovascular disease [ 28 ].…”
Section: Aadmentioning
confidence: 99%
“…VSMCs in TAAD changed the phenotype from contractile to synthetic, and enriched with the expression of elastin- and collagen-degrading MMPs at the site of dissection [ 31 ]. In addition, lysyl oxidase (LOX) is a copper-dependent amine oxidase that catalyzes the formation of cross-linking in collagen fibers and elastic lamellae [ 27 ]. β-Aminopropionitrile (BAPN)-treated animals have been widely used as a model of AAD.…”
Section: Aadmentioning
confidence: 99%